(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2025)
Osteoarthritis is a degenerative cartilage disease, induced by multiple factors, including aging and mechanical or inflammatory stress. During disease progression, bone tissue is affected, leading to osteochondral defects. Traditional and systemically applied treatments, often reveal limited success creating the need for more targeted approaches. In this context hydrogels can be used to manufacture vital implants e.g. by digital light (DLP) bioprinting. This technology allows to print precise implants loaded with cells, bioactive factors or photoactive delivery systems by UV mediated gelation of hydrogels. The biophysical properties of marine biopolymers may offer advantages for this technology not yet explored. In this study, we printed marine polymer-based 3D constructs including vital osteogenic cells. Bioprinting was performed using methacrylated alginate combined with jellyfish collagen in different concentrations for the hydrogels. Bioinks included a photoabsorber and photoinitiators as reported elsewhere1. 3*106 osteogenic cells/ml were mixed with the bioinks. The printing process was performed using a Lumen X at 37 °C. The STL file for the construct (h: 3.64 mm, d: 7 mm) was designed with 500 and 2000 µm pores. After printing, the constructs were additionally crosslinked with 50 mM CaCl2. Cellular viability and morphology was investigated using calcein-AM/Hoechst, staining for focal adhesion kinase/actin and confocal microscopy, DNA quantification, and scanning electron microscopy at different time points. Methacrylated alginate showed excellent properties for DLP printing; however it lacks binding sites for cell adhesion and thus profits from combination with other extracellular matrix components such as collagen. The use of rat collagen for bioprinting at 37 °C is difficult due to gelation above 20°C. However, experiments indicated that the use of marine collagen (lower melting point) is beneficial and supports the viability of cells in the investigated time frame. Calcein-AM, DNA quantification and SEM indicated cellular viability and a bone cell like morphology over 14 days. CaCl2 for additional crosslinking was essential to ensure stability of the constructs.